Measuring Colorado Superintendents’ Perceptions of Principal Preparation Programs - Spencer C. Weiler; Martha Cray (Educational Considerations, 2012)
Over the years, many scholars have criticized traditional leadership preparation programs for failing to produce qualified educational leaders capable of moving public education into the 21st century.
Keywords: Colorado; Superintendents; Principal; programs; literature; students; online; instruction